Challenges to seismic rehabilitation decision process in New Zealand: a focus of decision environment - Ying, Fei J.; Wilkinson, Suzanne; Corner, Jim (International Journal of Strategic Property Management, 2016)
Implementing seismic rehabilitation requires a substantial investment for substandard building owners. Seismic retrofitting can significantly reduce earthquake damages to the built environment and thus decrease the risk posing to the public and the community. However, many countries with active seismic zones, including New Zealand, experience slow progress of seismic retrofit. This paper examines the decision environment which has significant impact on stakeholders’ behaviours, to identify challenges in seismic rehabilitation decision-making. A qualitative approach was adopted with semi-structured interviews. A selection of building owners, government officials, and practical professionals involved in seismic retrofitting decision-making were interviewed. Major challenges identified by the interview results include various options, diverse considerations, assorted stakeholders, conflicting multiple objectives, and unaided decision making process. The inconsistency in expectation of whether building owners have sufficient aid in decision-making process offers plausible explanation regarding the key impediment to successful seismic rehabilitation decisions. A decision-making model is thus a necessity to assist building owners making an informed decision.